Efektivitas Kitosan Cangkang Keong Mas (Pomacea canaliculata) terhadap Penurunan Logam Timbal (Pb) Kerang Darah (Anadara granosa) - Setiawan, Nonny; Sarofah, Ulya; Priyanto, Anugerah Dany (Jurnal Ilmu Pangan dan Hasil Pertanian, 2020)
Blood clam (Anadara Granosa) is an important fishery commodity and is favored by the people around Kenjeran Beach, Surabaya. Blood clams can accumulate heavy metals such as Pb due to their living in sediments. Chitosan which comes from golden snail shells can bind Pb metal levels in blood clams. The purpose of this study was to determine the effect of concentration treatment and soaking time of gold snail shell chitosan on the reduction of blood clam Pb metal. Chitosan was produced by deproteination with 4% NaOH, demineralization with 1.25 N HCL, and deacetylization of chitin with 60% NaOH solution. The deacetylization degree of golden snail shell chitosan was 77.38%. The experimental design used was factorial CRD with two factors. The first factor was the concentration of chitosan (1%, 2% and 3%), while the second factor was the soaking time of the chitosan (90 minutes, 120 minutes, and 180 minutes). The data obtained were analyzed by ANOVA, if there were significant differences, then continued with the Duncan Test (DMRT). The best treatment produced was with a concentration of 3% chitosan and 180 minutes of soaking time for chitosan which reduced the Pb metal content of blood clams by 96.93%.